2020
DOI: 10.1016/j.toxlet.2020.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative elucidation of maternal-to-fetal transfer of neonicotinoid pesticide clothianidin and its metabolites in mice

Abstract: First quantitative study of fetomaternal transfer of CLO and its metabolites  Highly accurate quantification using LC-MS/MS analysis  Clear demonstration of the rapid passage of CLO through the placental barrier  Metabolite-dependent differences observed in blood pharmacokinetics and residual levels *Highlights (for review) -1-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Another NN, imidacloprid, has been reported to cause significant changes in ovarian morphology and in follicle stimulating hormone (FSH), luteinizing hormone (LH), and progesterone levels in female rats [ 21 ] and to decrease testosterone levels in male rats [ 12 ]. We recently reported that CLO passes rapidly through the placental barrier in mice [ 27 ]. It has also been shown that in utero and lactational exposure to CLO decrease the numbers of germ cells in male mice [ 44 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another NN, imidacloprid, has been reported to cause significant changes in ovarian morphology and in follicle stimulating hormone (FSH), luteinizing hormone (LH), and progesterone levels in female rats [ 21 ] and to decrease testosterone levels in male rats [ 12 ]. We recently reported that CLO passes rapidly through the placental barrier in mice [ 27 ]. It has also been shown that in utero and lactational exposure to CLO decrease the numbers of germ cells in male mice [ 44 ].…”
mentioning
confidence: 99%
“…C57BL/6NCrSlc pregnant mice were purchased from Japan SLC (Hamamatsu, Japan) and maintained as described elsewhere [ 27 ]. This study was approved by the Institutional Animal Care and Use Committee (Permission #26-05-07) and carried out according to the Kobe University Animal Experimental Regulations.…”
mentioning
confidence: 99%
“…Despite the lack of studies on contaminants in actively reproducing female bats and/or their offspring, it is probable that pups can be exposed in utero based upon numerous studies in humans and other mammals documenting placental transfer of commonly sold pesticides including neonicotinoids [58][59][60]. Furthermore, because pesticides and their metabolites are often detected in mammalian milk [61][62][63], pups are likely exposed to pesticides for approximately 3-4 weeks after birth while nursing.…”
Section: Reproductionmentioning
confidence: 99%
“…It appears that current environmental concentrations of NNs are relatively low and may not pose a health risk to adult humans. However, they could pose a risk to fetuses, as human and rodent studies have shown that both NNs and their metabolites can be transferred rapidly through the placenta and accumulate in the fetus [57,250,252]. Since during brain development the BBB of fetuses and neonates is immature, this will facilitate the penetration and accumulation of different chemicals, such as pesticides, in their brain [253].…”
Section: Relevance Of Daily Human Exposure To Pesticides Nnsmentioning
confidence: 99%